2014
DOI: 10.1111/petr.12296
|View full text |Cite
|
Sign up to set email alerts
|

Novel protocol including liver biopsy to identify and treat CD8+ T‐cell predominant acute hepatitis and liver failure

Abstract: In the majority of children with ALF, the etiology is unknown and liver transplantation is often needed for survival. A patient case prompted us to consider that immune dysregulation may be the cause of indeterminate acute hepatitis and liver failure in children. Our study includes nine pediatric patients treated under a multidisciplinary clinical protocol to identify and treat immune-mediated acute liver injury. Patients with evidence of inflammation and no active infection on biopsy received treatment with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
2
36
0
1
Order By: Relevance
“…This study demonstrates that a histopathologic feature, specifically CD8 staining, differentiates iPALF from dPALF cases. Our findings agree with those of McKenzie et al, who published a case series of patients with iPALF (n = 7) and acute hepatitis (n = 2) thought to have immune dysregulation and found to have numerous CD8 + T‐cells on IHC staining of liver biopsies . Similarly, Patel et al reported a CD8 predominant T‐cell infiltrate on IHC staining of liver tissue from 5 patients with iPALF .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This study demonstrates that a histopathologic feature, specifically CD8 staining, differentiates iPALF from dPALF cases. Our findings agree with those of McKenzie et al, who published a case series of patients with iPALF (n = 7) and acute hepatitis (n = 2) thought to have immune dysregulation and found to have numerous CD8 + T‐cells on IHC staining of liver biopsies . Similarly, Patel et al reported a CD8 predominant T‐cell infiltrate on IHC staining of liver tissue from 5 patients with iPALF .…”
Section: Discussionsupporting
confidence: 86%
“…We found that all 3 iPALF patients in our study who developed AA and had peripheral blood flow cytometry available had a decreased CD4:CD8 ratio (due to an increase in CD8 cells), and this finding has been reported in other studies of hepatitis‐associated AA . In McKenzie et al, all iPALF and acute hepatitis patients had a low CD4:CD8 ratio by peripheral blood flow cytometry, 3 of whom developed AA . We propose that a low CD4:CD8 ratio is an additional biomarker of the iPALF immune dysregulation phenotype as well as of those iPALF patients who are more likely to develop AA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with iPALF have a liver injury pattern similar to observations in familial and sporadic HLH and MAS . However, iPALF patients do not manifest the full spectrum of criteria required for diagnosis of HLH.…”
Section: Inflammatory Milieu In Palfmentioning
confidence: 99%